The Effect Of Supply Chain Risk on Resilience: Mediation Role of Supply Chain Integration - Mariam Mahira; Wahyuningsih Santosa; Triwulandari SD (Journal of International Trade, Logistics and Law, 2023)
This study aims to examine the effect of supply chain risk on supply chain resilience through the mediation of supply chain integration. A sample was collected by purposive sampling, and the data was gathered by using an online survey for three company sectors: manufacturing, logistics, and supply chain management in Java, Indonesia. The data were analyzed with Analysis of Moment Structure structural equation modeling (AMOS-SEM) using AMOS-24. The Result shows that SCR has impact to 3 dimension of integration but only Internal integration impact positively to SCRE whereas supplier and customer integration have not any impact on SCRE. Despite that, SCR still has an effect on SCRE, mediated by SCI. It’s suggest to improve the collaboration and coordination between Supplier and Customer Integration for Resilience of supply chain.